2007
DOI: 10.1002/app.26501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition and component structure on thermal behavior and miscibility of polypropylene catalloys

Abstract: ABSTRACT:The thermal behavior and the miscibility of an in-situ polypropylene blend named polypropylene catalloys (PP-cats) were investigated by using modulated differential scanning calorimeter (MDSC). It is found that all PP-cats samples present two glass transitions, one of which is ascribed to the ethylene-propylene random copolymer (EPR), and the other, to isotactic polypropylene (PP). However, no glass transition of ethylene-propylene block copolymer (E-b-P) responsible for a third component in PP-cats c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Figure 1(a) gives the reversible heat flow of IPC sample. It can be found that there appear two T g s. The higher T g should be attributed to the propylene homopolymer, and the other, to EPR, according to the previous reports 17–19. Even it has been reported that IPC contains ethylene‐propylene block copolymer as a third component,19 the T g of this block copolymer is difficult to be determined.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 1(a) gives the reversible heat flow of IPC sample. It can be found that there appear two T g s. The higher T g should be attributed to the propylene homopolymer, and the other, to EPR, according to the previous reports 17–19. Even it has been reported that IPC contains ethylene‐propylene block copolymer as a third component,19 the T g of this block copolymer is difficult to be determined.…”
Section: Resultsmentioning
confidence: 88%
“…It can be found that there appear two T g s. The higher T g should be attributed to the propylene homopolymer, and the other, to EPR, according to the previous reports 17–19. Even it has been reported that IPC contains ethylene‐propylene block copolymer as a third component,19 the T g of this block copolymer is difficult to be determined. The reasons for these results are involved in two factors: one is that the T g of the block copolymer is the same with that of the EPR or propylene homopolymer, hence the transition of the block copolymer is covered by that of other components; the other is that the content of the block copolymer in IPC is too low.…”
Section: Resultsmentioning
confidence: 88%
“…Since the discovery of Catalloy process by Himont company, polypropylene (PP) in‐reactor alloy has attracted many researchers because of its good balance in tensile strength and impact strength 1, 2. To further optimize the properties of PP in‐reactor alloys, lots of studies have been devoted to the polymerization process, chain structure, crystallization behavior, and phase morphology of PP in‐reactor alloys 3–28. A two‐stage polymerization process (TSP) is commonly used to produce polypropylene/ethylene‐propylene random copolymer (PP/EPR) in‐reactor alloys: propylene homopolymerization followed by ethylene‐propylene copolymerization 29–32.…”
Section: Introductionmentioning
confidence: 99%
“…6 9 Over the last decades, copolymerization has been realized as effective approaches to improve physical and mechanical properties of polymeric materials. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Over the last decades, copolymerization has been realized as effective approaches to improve physical and mechanical properties of polymeric materials. 10,11 Block copolymers can form meso structures at the nanometer-length scale, which has been the subject of intense research for the past four decades. Recently, constructing block copolymers with hierarchical structures has been the new focus of research.…”
Section: Introductionmentioning
confidence: 99%